Anemia and iron deficiency in primigent parturients in a municipality of Brazilian west Amazon. Issue 44 (30th October 2020) - Santos, Maria Tamires Lucas dos; Costa, Kleynianne Medeiros de Mendonça; Bezerra, Italla Maria Pinheiro; Santos, Edigê Felipe De Sousa; Szarfarc, Sophia Cornbluth; Rocha Pereira, Maria José Francalino da; Abreu, Luiz Carlos de; Venancio, Daniel Paulino
Abstract : Abstract: To analyze the prevalence of anemia and associated factors in primiparous parturient. Cross-sectional study conducted in a municipality of the Brazilian Western Amazon from July 2014 to December 2015. A convenience sample of 461 first-time pregnant women were interviewed. Data on their sociodemographic, clinical, obstetric, personal habits and nutritional status were collected. Anemia and iron depletion were measured by peripheral blood collection with hemoglobin, hematocrit, serum ferritin and transferrin saturation index. To test the association between the variables, the χ 2 tests were applied and Poisson regression analysis with a 95% confidence interval was performed, and P  < .05 values were considered significant. The Forward stepwise strategy was used to construct the adjusted model. These analyzes were performed using the STATA 14.0 program (College Station, TX, 2013). A higher risk of anemia was identified among adolescent; white; who had a partner; with unpaid occupation, with less than eight years of formal education. Residents in the countryside; smokers; who had more than six prenatal consultations and were overweight. Anemia was reported in 28.20% and iron depletion in 60.52% of parturient women. The variables studied did not have association with the anemia outcome, except alcohol consumption.